Effect of Temperature and Relative Humidity on Crop Yield in Tropical Greenhouse with Evaporative Cooling System - Jamaludin, Diyana (2009)
Tropical greenhouses require active evaporative cooling system such as pad-and-fan to ensure a suitable microclimate for crop production. Excess heat causes indoor temperature becoming hotter than desired resulting in detrimental effects to crop growth and production. Solar radiation intensity and outside temperature affect temperature and relative humidity level inside the greenhouse while wide gradients in temperature and relative humidity can cause problems for crop growth and production uniformity. Horizontal and vertical profiles of temperature and relative humidity inside the greenhouse were investigated. The study showed that temperature increased from evaporative pad to exhaust fans in a horizontal direction while relative humidity shows inverse pattern from temperature. In the vertical direction, temperature increased, while relative humidity decreased from lower level to the upper level. Similar pattern of temperature and humidity distribution were observed inside the greenhouse, regardless of whether it was empty or with growing crop. The inside temperature with growing crops however, was slightly lower than the empty greenhouse. ANOVA results shows that in overall, temperature and relative humidity inside the greenhouse were uniform as there’s no significance difference at 95% confidence interval. The effects of temperature gradients inside the greenhouse and time of highest sunlight received on canopy diameter, head weight and head diameter were evaluated. Based on the results, most of the crop quality was better near the evaporative pad area as it was much cooler and east area which received highest morning sunlight (9am-11am). ANOVA test shows that crop yield inside the greenhouse was significantly different between each sections which shows that it was greatly affected by difference in temperature and relative humidity. A mathematical equation representing the inside temperature was developed for both empty greenhouse and greenhouse with growing crops. Both measured and calculated values of inside temperature show strong agreement with R2 = 0.996 for empty greenhouse and R2 = 0.945 for greenhouse with growing crops. The t-test for calculated and measured inside temperature values of both conditions show no significant difference between them.